FEMININITAS GEISHA DALAM NOVEL ARTHUR GOLDEN MEMOIRS OF A GEISHA - Rahayu, Mundi (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Geisha is an entertaining artist in Japan during Edo period (1603-1868) when cities were growing up and wealthy spread out among merchant class. The wealthy was followed by the building of teathers, restaurants, clothes and several entertaining places. Then, the identity of womanship for a geisha can be easily recognized through her beautiful and elegant performance. This sort of performance which makes geisha is different from other commercial worker women. Her feminity is also shown by her ability to entertain original japanese society that is her ability to play japanese traditional music tools such as drum and shamisen. She is also able to sing and dance. She has also the ability in dringking tea ceremony service. Geisha’s feminity is relatively similar with women’s feminity in common which is agreed by society. What makes them different is that geisha’s feminity is developed professionally and is made as survival way and even as an access to get into broader economics and politics. Ironically, to some extent, that brings a risk for a geisha due to her position as a client for her patronage.